Renal Effects of SGLT‐2 Inhibitors and Other Anti‐diabetic Drugs: Clinical Relevance and Potential Risks. Issue 3 (21st July 2017) - Lioudaki, E; Whyte, M; Androulakis, ES; Stylianou, KG; Daphnis, EK; Ganotakis, ES
Abstract : Type 2 diabetes mellitus (T2DM) is a metabolic disease affecting an increasing percentage of general population worldwide. Patients with T2DM are frequently characterized by impaired renal function, primarily as a result of diabetic kidney injury, but also by other contributing factors, such as hypertension, atherosclerosis, and medications. Sodium‐glucose cotransporter (SGLT)‐2 inhibitors have emerged as a new, promising class of antidiabetic agents with actions that seem to extend beyond their hypoglycemic effect.